Scaling success: Expanding community-based breeding programs for sheep and goats in Ethiopia - Tolemariam, Taye; Abegaz, Solomon; Getachew, Tesfaye; Haile, Aynalem; Mourad, Rekik; Belay, Berhanu; Rischkowsky, Barbara A. (2024)
The first community-based breeding programs (CBBPs) were launched in 2009, with limited participation in six model villages focusing on three sheep breeds: Bonga, Menz, and Horro (Haile et al., 2019). The program was primarily facilitated through research centres. However, participation steadily increased. Between 2014 and 2021, there were 73 villages and 7,278 households under the CBBP (Getachew et al., 2024). Based on the successful implementation of the program in previous years and the involvement of ICARDA, along with regional and national research institutions and Universities, the number of participating households and flock size saw significant growth from 2022 to 2024. The number of families involved in the CBBP rose to 7,329 in 2022, 8 980 in 2023, and 10,052 in 2024, with 40,309, 49,390, and 55,269 beneficiaries in 2022,2023, and 2024, respectively. The flock size of small ruminants under CBBP also significantly increased by almost ten thousand (ninety-fold) in each of the subsequent three years. Similarly, the number of villages under CBBP has increased dramatically, reaching 101, 120, and 139 villages in 2022, 2023, and 2024, respectively (Table 1). Considering the distribution of CBBPs across the institution, the number of villages under the research system declined slightly from 2022 to 2023 (82 vs 80) but increased by 12 during 2024 (92). In contrast, villages under the Universities have shown an increasing trend over the three years due to the involvement of additional universities and/or expansion of villages (Table 2). The scaling approach adopted by the Sustainable Animal Productivity for Livelihoods, Nutrition, and Gender Inclusion (SAPLING) initiative, in partnership with the International Center for Agricultural Research in the Dry Areas (ICARDA), successfully expanded the implementation to 141 production unit villages, benefiting 9,212 households. This effort is closely tied to the community-based breeding programs (CBBPs), which provide improved genetic materials (Getachew et al., 2024). The growth of the CBBPs in terms of the number of villages and households, coupled with the collaboration of various stakeholders, highlights the program's success and widespread acceptance within the community.